Integrating Pedagogy and Practice: The Impact of Academic Service Learning in the TEFL Context in Higher Education - Chen, Ai-hua (Education as Change, 2023)
This study explored the transformative potential of academic service learning (ASL) within a Taiwanese university setting in the context of teaching English as a foreign language. The participants were students majoring in English, enrolled in a semester-long English teaching course. Their academic service-learning project involved teaching English to students in rural primary schools. By adopting both quantitative and qualitative approaches, this study illuminated how ASL influences students’ academic, personal, and interpersonal development. Quantitative findings revealed a significant level of satisfaction with the ASL course and noted substantial gains in personal growth, professional development, and civic engagement domains. As for the qualitative data, the study brought forth the concrete ways in which the academic service-learning curriculum has augmented students’ professional knowledge, skills, and attitudes. While the results aligned with many previous studies asserting the benefits of service learning in enhancing academic and practical learning outcomes, they also shed light on the potential areas of improvement, particularly in fostering civic engagement. Overall, this study underscored the transformative potential of a well-structured academic service-learning curriculum in enriching student learning experiences, bridging the gap between theoretical knowledge and real-world application, and cultivating a deeper sense of civic responsibility.